Memikirkan Kembali Kebijakan Pertahanan di Era Peperangan Siber - Sarjito, Aris (Jurnal Publisitas, 2023)
The evolution of technology and the increased reliance on the internet and digital infrastructure have given birth to a new threat to national security- cyber warfare. Unlike traditional warfare, cyber warfare poses unique challenges for nations, making it a pressing issue for the defense policies of countries across the globe. The aim of this qualitative research is to examine the unique challenges posed by cyber warfare and how they differ from traditional forms of warfare. The research will identify the ways in which defense policies can be adapted to effectively respond to cyber threats, and what personnel and skill sets are needed to overcome these challenges. The research will also explore methods of developing and training personnel to effectively respond to cyber threats. This research will utilize secondary data collection through academic journals, government reports, and other reputable sources to provide insight into the current state of cybersecurity and defense policies across the globe. The findings will highlight the unique challenges of cyber warfare, including the asymmetrical nature of the attacks, difficulty in monitoring and attribution of attacks, and the lack of international norms for cyber activities. The research emphasizes the need for rethinking defense policy in the era of cyber warfare and the need for a paradigm shift in the approach toward cyber threats. The research recommends the development of comprehensive, multi-dimensional defense strategies making use of advanced technologies for detection, prevention, and response. The findings also highlight the need for investing in personnel with technical and analytical skillsets to man critical positions in the cyber defense structure.